Noradrenaline goes nuclear: epigenetic modifications during long‐lasting synaptic potentiation triggered by activation of β‐adrenergic receptors. (21st December 2015) - Maity, Sabyasachi; Jarome, Timothy J.; Blair, Jessica; Lubin, Farah D.; Nguyen, Peter V.
Abstract : Key points: Transcription is recruited by noradrenaline in the hippocampus. Epigenetic mechanisms are recruited by hippocampal noradrenergic receptor activation. Epigenetic regulation by noradrenaline offers a novel mechanism for long‐term potentiation Abstract: Noradrenaline (NA) is a neuromodulator that can effect long‐lasting changes in synaptic strength such as long‐term potentiation (LTP), a putative cellular mechanism for memory formation in the mammalian brain. Persistent LTP requires alterations in gene expression that may involve epigenetic mechanisms such as DNA methylation, histone acetylation and histone phosphorylation. It is known that β‐adrenergic receptors and NA can boost LTP maintenance by regulating translation. However, it is unclear whether NA can additionally engage epigenetic mechanisms to regulate transcription and boost LTP endurance. To address this issue, we probed NA‐treated mouse hippocampal slices with pharmacological inhibitors targeting epigenetic regulatory pathways and discovered that NA activates β‐adrenergic receptors to boost LTP maintenance in area CA1 through DNA methylation and post‐translational histone modifications. Specifically, NA paired with 100 Hz stimulation enhanced histone H3 acetylation and phosphorylation, both of which were required for NA‐induced boosting of LTP maintenance. Together, our findings identify NA as a neuromodulatory transmitter capable of triggering epigenetic, transcriptional control of genes required for establishing persistent LTP in the mouse hippocampus. These modifications may contribute to the stabilization of memory. Key points: Transcription is recruited by noradrenaline in the hippocampus. Epigenetic mechanisms are recruited by hippocampal noradrenergic receptor activation. Epigenetic regulation by noradrenaline offers a novel mechanism for long‐term potentiation